2016
DOI: 10.1080/02671522.2016.1158855
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of national identity in post-conflict Northern Ireland: a comparison of different school settings

Abstract: It is generally accepted that education has a significant role to play in any society transitioning from conflict to a more peaceful dispensation. Indeed, some have argued that the education system potentially represents the single most effective agent of social change with the capacity to bridge ethnic division in conflict affected countries. Despite the potential, educational policy makers grapple with the dilemma as to precisely how school systems can best facilitate this agenda. This paper thus attempts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Common approaches to decreasing negative intergroup attitudes include increasing contact for individuals or small groups of children and adolescents. Although attempts have been made to integrate contexts such as schools for youth in Belfast, progress has been limited and many youth still live, learn, and work in segregated spaces (Furey, Donnelly, Hughes, & Blaylock, 2016;Shirlow & Murtagh, 2006). In addition to replicating findings that quality of contact at the personal level is related to lower intergroup bias, the current results suggest that neighborhood norms of contact that is frequent and high quality predict slower increases in intergroup bias.…”
Section: Resultsmentioning
confidence: 99%
“…Common approaches to decreasing negative intergroup attitudes include increasing contact for individuals or small groups of children and adolescents. Although attempts have been made to integrate contexts such as schools for youth in Belfast, progress has been limited and many youth still live, learn, and work in segregated spaces (Furey, Donnelly, Hughes, & Blaylock, 2016;Shirlow & Murtagh, 2006). In addition to replicating findings that quality of contact at the personal level is related to lower intergroup bias, the current results suggest that neighborhood norms of contact that is frequent and high quality predict slower increases in intergroup bias.…”
Section: Resultsmentioning
confidence: 99%
“…It is now the preferred option for 25% of citizens, making it the third most popular in the region, and the only one that is accepted by equivalent numbers of both Catholics and Protestants (ARK, ). The limited body of work that has investigated Northern Irish identification has shown that it tends to be associated with more conciliatory attitudes towards outgroup members and higher levels of intergroup contact (Furey, Donnelly, Hughes, & Blaylock, ; Hayes, McAllister, & Dowds, ). It is typically presented as a “common ingroup identity” (a superordinate identity that is inclusive and composed of two or more subordinate social categories) due to its perception of inclusivity (Hayes & McAllister, ; Lowe & Muldoon, ).…”
Section: Understanding the Nationmentioning
confidence: 99%
“…However, research indicates that children and young people are moving away from traditional identity labels (Ganiel, ). Further, there is a growing body of research to suggest that pupils attending integrated schools reject more traditional identities and allegiances on issues such as national identity and constitutional preferences (Hayes et al ., , ; Furey et al ., ). Researching young people who have chosen to disidentify with their community background, favouring an alternative to the traditional bipartite system, presents a unique challenge.…”
Section: Discussionmentioning
confidence: 97%